A signal boosting technique for gene prediction - Gunawan, Teddy Surya; Ambikairajah, Eliathamby; Epps, Julien (IEEE Xplore, 2007)
This paper presents the signal boosting technique for gene and exon identification of a DNA sequence. Newly proposed signal boosting technique is used to enhance the coding region and improve the likelihood of correctly identifying the coding region. This new method is compared with other genomic signal processing techniques, such as DFT, IIR anti-notch filter, and multistage filters. Results show that the ratio of coding to non-coding energy was enhanced by almost twice. Furthermore, the proposed method outperforms other methods in terms of sensitivity, specificity, and prediction rate, when testing with 78 sequences from HMR195 database.